P. A. Kupriyanov and his work at The First Medical Institute of Leningrad: «With deep insight into the nuances of the chosen specialty» - G. G. Khubulava; V. V. Sizenko; N. G. Luk’yanov; R. A. Akhadov; I. B. Oleksyuk; A. A. Zhuravlyov; I. M. Navaliyev (Учёные записки Санкт-Петербургского государственного медицинского университета им. Акад. И.П. Павлова)
Since 1926, Peter Andreevich Kupriyanov served at Z.P. Solovyov Central Red Army Military Hospital of Leningrad and simultaneously began to work part-time at Pavlov First Medical Institute of Leningrad. This article talks about the work of P.A. Kupriyanov at The First Medical Institute of Leningrad from 1926 to 1948.